2014
DOI: 10.5966/sctm.2013-0079
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow-Derived Mesenchymal Stem Cells Display Enhanced Clonogenicity but Impaired Differentiation With Hypoxic Preconditioning

Abstract: Stem cells are promising candidate cells for regenerative applications because they possess high proliferative capacity and the potential to differentiate into other cell types. Mesenchymal stem cells (MSCs) are easily sourced but do not retain their proliferative and multilineage differentiative capabilities after prolonged ex vivo propagation. We investigated the use of hypoxia as a preconditioning agent and in differentiating cultures to enhance MSC function. Culture in 5% ambient O(2) consistently enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 95 publications
12
99
0
Order By: Relevance
“…However, MSCs often reside in niches of low oxygen in vivo: 1-7% in BM, 10-15% in adipose tissue, and 2.5-8.5% in placenta (Bizzarri et al 2006;Schneider 2011;Boyette et al 2014). Moreover, MSCs always participate in bone healing under low oxygen microenvironment in vivo (Dimitriou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, MSCs often reside in niches of low oxygen in vivo: 1-7% in BM, 10-15% in adipose tissue, and 2.5-8.5% in placenta (Bizzarri et al 2006;Schneider 2011;Boyette et al 2014). Moreover, MSCs always participate in bone healing under low oxygen microenvironment in vivo (Dimitriou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained tissue exhibited high positive staining for cartilage ECM components: glycosaminoglycans, collagen II, and lubricin [45][46][47][48]. Note that, however, positive staining was also obtained for the collagen X, which is well-known as a marker of hypertrophic chondrocytes and produces calcified cartilage [45].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Note that, however, positive staining was also obtained for the collagen X, which is well-known as a marker of hypertrophic chondrocytes and produces calcified cartilage [45].…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that oxygen seems to play a marked role in amplifying the alterations in "adhesion and communication" pathways, common features in all of the sim-μg experiments. Considering the actual interest in the role of oxygen concentration in the proliferation, differentiation, and senescence events (Boyette et al 2014), we evaluated whether different O 2 tensions in sim-μg affect also human BMSCs that we selected for the SCD experiment. We chose a focused array, the Human Mesenchymal Stem Cell RT 2 Profiler™ PCR Array (SABiosciences) that profiles the expression of 84 key genes involved in human MSC pluripotency, self-renewal status and differentiation.…”
Section: %°O2mentioning
confidence: 99%